Evaluation of the Effectiveness of Esterified Hyaluronic Acid Fibers on Bone Regeneration in Rat Calvarial Defects - ÖZBEYLİ, DİLEK; ÖZTÜRK ÖZENER, HAFİZE; YILDIRIM, HATİCE SELİN; KÖSE, KEMAL NACİ; KURU, LEYLA; AĞRALI, ÖMER BİRKAN (HINDAWI LTD, 2018)
Hyaluronic acid (HA) constitutes one of the major components of the extracellular matrix domain in almost all mammals. The aim of this study was to evaluate the regenerative capacity of HA matrix in rat calvarial bone defects and compare with those of different combinations of resorbable collagen membrane (M) and bovine-derived xenograft (G). Twenty-four 3-month-old male Sprague-Dawley rats weighing 200-250 g were included. Control group was created by leaving one defect empty from 2 critical size defects with 5 mm diameter formed in the calvarial bones of 8 rats. In the same rats, the other defect was treated with HA matrix alone. One of the 2 defects formed in other 8 rats was treated with HA + G and the other with HA + M. One of the 2 defects formed in the remaining 8 rats was treated wilh G+M and the other with HA+G+M. The animals were sacrificed at 4 weeks. Histologic, histomorphometric, and immunohistochemical analyses were performed. Both HA matrix alone and its combinalions with G and M supported new bone formation (NBF). However, NBF was significantly greater in G+M and HA+G+M groups compared to control and HA alone (P < 0.00l). Bone morphogenetic protein-2 was expressed with varying degrees in all groups, without any difference among them. Within the limitations of the present study, HA matrix, used alone or in combination with G and M, did not contribute significantly to bone regeneration in rat calvarial bone defects.
Keywords: MOLECULAR-WEIGHT; IN-VITRO; DELIVERY; DEGRADATION; HYDROGELS; MARROW; PROLIFERATION; AUGMENTATION; EXPRESSION; IMPLANTS